DIE REFORMIERTE BEERDIGUNGSLIEDER UND - BRÄUCHE DES GEBIETES AM BACH NÁDAS - Miklós-Csaba GYÖRGYJAKAB (Studia Universitatis Babeş-Bolyai. Musica)
The Reformed Funeral Songs and Territorial Customs in the Nádas River Area. In this paper I will present the customs regarding the Hungarian reformed funeral songs in the area by the stream Nádas, an area that is located in the heart of Kalotaszeg in Romania. The paper follows a theoretical and a practical thread. In the theoretical part I examined the funeral song-material of old Hungarian song collections, while the practical part describes my visits to a number of villages with significant folk traditions, inhabited by Hungarians, where I collected and summarized the musical traditions associated with funerals. In this paper I will shortly report on my findings, observations and experiences.